Optimisation of Ultrasonic-Assisted Extraction (UAE) of Allicin from Garlic (Allium sativum L.) - Mathialagan, R. (Italian Association of Chemical Engineering - AIDIC, 2017)
Garlic (Allium sativum L.) is one of the most widely used traditional medicines. Allicin is the main bioactive components of garlic which is responsible for many of its benefits, such as antimicrobial, anti-inflammatory and antioxidant agent. This study investigated the ultrasound-Assisted extraction (UAE) of allicin from garlic. The extraction conditions associated with allicin yield, including particle size, extraction temperature and extraction time, are discussed. HPLC has been used for the quantification of allicin. The optimal condition for the extraction of allicin from garlic was found with sliced garlic, at temperature of 25 °C and 90 min of extraction for the maximum yield (112 μg/mL). Overall, the results obtained indicate that UAE method provided a good alternative for the extraction of allicin from garlic. Copyright © 2017, AIDIC Servizi S.r.l..